Mitigation of Unbalanced Voltage Sags and Swells of Power System in Utility Side by using Sen Transformer - Rao Burthi, Loveswara; S.Prema Kumar, P (International Journal of Engineering and Technology, 2018)
Majority of the industrial electrical loads requires balanced three phase supply but in reality there is unbalanced supply due to single phase loads like railway tracks etc.increasing use of non linear loads in modern power distribution network there are some power quality issues like voltage sags and voltage swells, this distortion of the power supply effect the loads which are connected to power distribution network. In order to improve quality of the power, in this paper a Sen Transformer (ST) technique as been proposed to minimize unbalanced voltage sags and swells. The proposed technique mitigates both voltage sag and swell during balanced and unbalanced operating conditions. The proposed ST consists of a programmable tap controller to compensate ride through faults in power system network. The proposed work as been implemented using MATLAB/SIMULINK software. To validate the proposed work, simulation results are presented.Â Â